Possibility of Implementing Digitization of Notarial Authentic Deeds as Electronic Evidence - Putu Sinthya Alyandi; Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The aim of this article is to examine the usage of cyber notary, which has not been effective because of the vague standards surrounding the concept of cyber notary, including its definition and rules. Additionally, the article aims to assess the feasibility of incorporating cyber notary into traditional notary practices. The method used in this research is normative legal research. The results of this article are: First, there is a need for legal harmonization or re-actualization of rules between UUJN/UUJN-P and the ITE Law so that they can serve as a legal framework regulating the digitalization of authentic deeds, and notarial deeds can be categorized as valid electronic documents under the ITE Law. Second, the implementation of digitizing authentic notarial deeds is based on fulfilling legal needs in the notary sector, which extends beyond the formulation of rules regarding cyber notary to include the digitization of authentic deeds and notaries' obligations in executing cyber notary duties.